Photoreceptor damage in Terson syndrome - Szeligowski, T; Fu, DJ; Fernandez-Ledo, N; Birtel, J; Aslam, SA; Patel, CK; Xue, K; Charbel Issa, P (Wolters Kluwer, 2023)
Purpose: To describe photoreceptor damage in patients with Terson syndrome as a potential cause for inconsistent clinical outcomes. Methods: Clinical evaluation and retinal imaging in six patients Results: Four patients were female and two male, with an average age of 46.8 years (SD 8.9). Four patients suffered aneurysmal subarachnoid haemorrhage, one vertebral artery dissection, and one superior sagittal sinus thrombosis. In 11 eyes, we observed a consistent pattern of outer retinal damage within the central macula affecting the ellipsoid zone and the outer nuclear layer, indicating photoreceptor damage. Areas of photoreceptor damage showed poor spatial correlation with intraocular haemorrhage, particularly sub-internal limiting membrane haemorrhage. The observed retinal abnormalities demonstrated incomplete recovery over long-term follow-up 3.5 to 8 years post-haemorrhage, irrespective of surgical or conservative treatment strategy, and had variable impact on the patients’ visual function. Conclusion: The observations suggest that photoreceptor damage in Terson syndrome likely represents a distinct manifestation of this condition, which could be caused by transient ischaemia resulting from disturbed choroidal perfusion secondary to acute rise in intracranial pressure.